Foreword: A Bankruptcy Conference for the '90s - Daniel L. Keating (Washington University Law Quarterly, 1994)
This Symposium presents the papers and commentary that served as the basis for the lively exchange of the Conference itself. The Conference was held at the John M. Olin School of Business, Washington University, on February 25 and 26, 1994. The Conference was sponsored by the Washington University School of Law, and was funded in part through grants from the National Conference of Bankruptcy Judges' Endowment for Education and from the Business, Law, and Economics Center of the Olin School of Business at Washington University.